Горно-геологические факторы дегазации пород на шахте «Алмазная» - Пащенко, П.С.; Компаниец, А.А. (Геотехническая механика, 2012)
Описані основні чинники дегазації порід на вугільних шахтах. Серед цих чинників – центральні частини стародавніх русел і потоків; локальні структури; зони порушених порід. Поєднання вказаних чинників показує зони скупчення вільного газу у відкладах шахт. Одержані експериментальні дані про розподіл газу в покрівлі основного вугільного пласта на шахті «Алмазна». Basic factors of the rock degassing in the coal mines are described. Among these factors are central parts of ancient canals and streams; local structures; areas of broken rocks. Combination of these factors indicates areas with free gas accumulation in the mine deposits. Experimental findings on gas distributing in the roof of basic coal layer in the Almaznaya mine are presented.